Crossing Over. Trinidad farewell song interlude - Bampoe-Addo, Wallace; Laird, Christopher; Layne, Lancelot, -1990; Beddoe, Andrew; Nimo, Ko, 1934-; NAFTI of Ghana; Banyan Production (Firm) (Trinidad and Tobago : Banyan Archive, 1988)
Lancelot Layne closing up his house and leaving; Koo Nimo (Daniel Amponsah) sitting in the van looking out and thinking as it drives past the Queen's Park savannah; Koo Nimo (Daniel Amponsah) and Lancelot Layne sitting in a cocoa field singing the farewell song to end the programme; Immortelle tree in bloom.
Title from resource description page (viewed October 21, 2022).
In English.
Keywords: Music -- Trinidad and Tobago; Trinidad and Tobago -- Social life and customs; Trinidad and Tobago -- Religious life and customs; Musique -- Trinité-et-Tobago.; Trinité-et-Tobago -- Mœurs et coutumes; Trinité-et-Tobago -- Vie religieuse; Manners and customs; Music; Trinidad and Tobago; documentary film; Documentary films; Unedited footage; Documentary films; Unedited footage; Documentaires